The Assessment of Components Affecting Interest in Reusing Video Conferencing Advancement - Fitriani Reyta; Susan Purnama; Bob Foster; Aggi Panigoro Sarifiyono; Teguh Rahman Faiz; Wulan Julfiani (Britain International for Academic Research (BIAR) Publisher, 2024)
In the new normal era, the use of video conferencing technology has increased and become a new habit among Indonesians. However, despite a significant increase, the factors influencing the interest in reusing video conferencing technology after the new normal era are still in question. Thus, this study aimed to create a research model to explain factors influencing the interest in reusing video conferencing technology, including perceived ease of use, usefulness, self-efficacy, enjoyment, social influence, facilitating conditions, and user satisfaction. The population in this study was people who live in the Greater Jakarta area, with a total of 320 samples collected using the purposive sampling method through questionnaires on google forms. Then the data was processed using PLS. The results of data analysis using the structural equation modeling method show that self-efficacy and facilitating conditions have a positive effect on perceived ease of use, perceived enjoyment and social influence have a positive effect on perceived usefulness, system quality has a positive effect on user satisfaction, perceived ease of use has a positive effect on perceived usefulness, perceived usefulness has a positive effect on continuance intention, perceived usefulness has a positive effect on user satisfaction, and user satisfaction have a positive effect on continuance intention. However, perceived ease of use has an insignificant effect on continuance intention in reusing video conferencing technology.